Surveillance of Bat Coronaviruses in Kenya Identifies Relatives of Human Coronaviruses NL63 and 229E and Their Recombination History - Tao, Ying; Shi, Mang; Chommanard, Christina; Queen, Krista; Zhang, Jing; Markotter, Wanda; Kuzmin, Ivan V; Holmes, Edward C; Tong, Suxiang (Journal of virology, 2017)
Bats harbor a large diversity of coronaviruses (CoVs), several of which are related to zoonotic pathogens that cause severe disease in humans. Our screening of bat samples collected in Kenya from 2007 to 2010 not only detected RNA from several novel CoVs but, more significantly, identified sequences that were closely related to human CoVs NL63 and 229E, suggesting that these two human viruses originate from bats. We also demonstrated that human CoV NL63 is a recombinant between NL63-like viruses circulating in bats and 229E-like viruses circulating in bats, with the breakpoint located near 5' and 3' ends of the spike (S) protein gene. In addition, two further interspecies recombination events involving the S gene were identified, suggesting that this region may represent a recombination "hot spot" in CoV genomes. Finally, using a combination of phylogenetic and distance-based approaches, we showed that the genetic diversity of bat CoVs is primarily structured by host species and subsequently by geographic distances. Understanding the driving forces of cross-species virus transmission is central to understanding the nature of disease emergence. Previous studies have demonstrated that bats are the ultimate reservoir hosts for a number of coronaviruses (CoVs), including ancestors of severe acute respiratory syndrome coronavirus (SARS-CoV), Middle East respiratory syndrome coronavirus (MERS-CoV), and human CoV 229E (HCoV-229E). However, the evolutionary pathways of bat CoVs remain elusive. We provide evidence for natural recombination between distantly related African bat coronaviruses associated with and sp. bats that resulted in a NL63-like virus, an ancestor of the human pathogen HCoV-NL63. These results suggest that interspecies recombination may play an important role in CoV evolution and the emergence of novel CoVs with zoonotic potential.